PENGUJIAN KINERJA MESIN DAN EMISI GAS BUANG MESIN DIESEL BERBAHAN BAKAR EMULSI PADA BERBAGAI TEKANAN INJEKSI - Mangalla, Lukas Kano; Suardjaja, I Made (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
The aim of this research is to examine the effect of increasing injection pressure on engine performance and exhaust emission of emulsified fueled diesel engine. The diesel exhaust emission such as Nitrogen Oxide (NOx), Carbon Monoxide (CO), Unburned Hydrocarbon (HC) and Soot can be controlled through complete combustion and lower peak combustion temperature. This phenomenon occurred by utilizing fuel-water emulsion at high injection pressure to obtain a good atomization and perfect mixing of fuel-air in combustion chamber. The engine employed in this research was four stroke single cylinder diesel engine, with bore of 75 mm and stroke 80 mm. Engine was operated at vary throttle position from 20%, 40%, 60%, 80% and 100%. At each throttle position rpm, load, fuel consumption, inlet pressure, exhaust temperature, carbon monoxide, unburned hydrocarbon and opacity were measured. CO-HC emissions are measured by Mexa 321E and opacity by LDR tester. The injection pressure of fuel was varied at 145, 170 and 195 kg/cm2. The concentration of water in emulsion fuel was varied of 0%, 10%, 20% and 30%W/O. ABS (Alkyl benzene Sulfonate) was used as emulsifier of water and diesel fuel with 0,22% volume. The result of the research show that torque and power of diesel engine were relatively constant with increasing injection pressure but emission of CO, HC and opacity reduced significantly. Increasing of injection pressure from 145 to 195 kg/cm2 resulted in reducing emission of CO, HC and opacity by 73 %, 60 % and 26.4 % respect-tively at wide-open-throttle.